SEMAUN DALAM BAYANG-BAYANG PEMERINTAH HINDIA BELANDA 1899-1923 (History Department, Semarang State University and Historian Society of Indonesia, 2011)
The background of Semaun life between 1899-1923 is influenced by the hands of the Dutch colonial government power, either directly or indirectly. His father who worked as a stone breaker at the Railway Bureau economically place them as disadvantaged and exploited social groups. Because they are only used as cheap labor. In the stratification of society in East Java, Dutch East Indies in particular, the Semaun is categorized as abangan Islamic family which is in everyday social intercourse are socially marginalized. Politically, Semaun family is not counted, except within the framework of the political interests of rulers in achieving its goals. In the field of education, Semaun can achieve it despite the limitations. Key words: Semaun, educational, economic, social and political Â Latar belakang kehidupan Semaun antara 1899-1923 dipengaruhi oleh tangan-tangan kekuasaan pemerintah kolonial Belanda, baik secara langsung maupun tidak langsung. Ayahnya yang bekerja sebagai pemecah batu di Jawatan Kereta Api Surabaya secara ekonomi menempatkannya pada golongan masyarakat kurang mampu dan tereksploitasi. Karena mereka hanya dijadikan tenaga kerja murah. Dalam stratifikasi masyarakat di Hindia Belanda khususnya Jawa Timur, keluarga Semaun masuk dalam kalangan Islam abangan yang dalam pergaulan sehari-hari termarginalisasi secara sosial. Secara politis, keluarga Semaun tidak masuk hitungan, kecuali dalam kerangka kepentingan politik penguasa dalam mencapai tujuannya. Dalam bidang pendidikan, Semaun dapat meraihnya walaupun dalam keterbatasan. Â Kata kunci: Semaun, pendidikan, ekonomi, sosial dan politik. Â